ACCOUNTING CONCEPTS AND STANDARDS. - Jones, Raplh Coughenour (The Accounting Review, 1950)
Abstract Although a revised statement of concepts and standards was published in 1948, a Committee on Accounting Concepts and Standards was appointed early in 1949. The appointment of a new committee so soon after the publication of a revision did not indicate an intention either to rewrite the 1948 statement immediately or to adopt a policy of introducing new models each year. The purpose clearly was to institute a continuous program of study and research, which it was felt might be more effective than the more or less spasmodic efforts of the past. The members of this committee favor such a program. Methods by which it can be made effective, however, have not yet been fully worked out. The committee has faced and still faces a dilemma arising out of the fact that it is not expected either to publish a revised statement in 1949 or to continue as a committee with the same membership until a revised statement is published. During the two-day meetings of this Committee, the discussion ranged over the whole field of accounting and revealed surprisingly broad areas of agreement, although the usual difficulties were met in phrasing statements, which would secure unanimous approval.